Human Rights in the Continental European Legal System in Indonesia - Putra Nasution, Andreansyah (Riviera Publishing, 2025)
Human Rights are fundamental rights that are inherent in every individual from birth. This right, which is naturally inrevocable because it is a gift from God Almighty, becomes one of the important aspects of human life. In this context, the Continental European Legal System is known to have a characteristic in the form of recognition of human rights. As a country of law based on Pancasila and democracy, Indonesia has a responsibility to protect these rights. The protection of human rights in a country of law must be regulated in the constitution and national law. This study uses a normative legal research method that aims to analyze legal regulations that are relevant to the issue under study, which focuses on conceptual and normative approaches that examine applicable laws and regulations, legal principles, and doctrines. This study concludes that Indonesia, as a legal country that refers to the legal system of Continental Europe, has comprehensively regulated the protection of human rights in the 1945 Constitution of the Republic of Indonesia, although challenges in the implementation and enforcement of the law still require more continuous attention.